THE IMPORTANCE AND PERFORMANCE ANALYSIS OF COMPENSATION PROGRAM IN REGIONAL OFFICE OF DJKN SULUTTENGGOMALUT AT MANADO - Imban, Yutika W. (Sam Ratulangi University, 2016)
ABSTRACT Today, the institutions have required to have qualified human resource in order to achieve their goals. Employees do not only determine what the institution will be, but also how it will grow to be better entity. The study aims to find the Importance and Performance Analysis of Compensation Program in Regional Office of DJKN Suluttenggomalut at Manado. The research type is a descriptive quantitative. 49 employees of Regional Office of DJKN Suluttenggomalut at Manado were surveyed as samples. The result shows the program in Quadrant I (TKPKN, Children Allowance, Wife/Husband Allowance) is important but the performance is not good to employee. Quadrant II (Salary, TUKIN and Meal Cost) the programs are important an have a good performance for the employee. InÂ Quadrant III (Rice Allowance)has a low of importance and perfoemance. In Quadrant IV (Overtime and Honorarium Team) the programs areÂ not important but have a good of performance to employee. Keywords: Compensation, Importance and Performance Analysis